1998
DOI: 10.1002/(sici)1521-396x(199802)165:2<517::aid-pssa517>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of Z-Bands in CdTe

Abstract: We have studied the photoluminescence band shape of the 1.36 eV (Z‐band) and the 1.32 eV (Z′‐ band) PL bands in high purity low‐temperature‐grown n‐type bulk polycrystalline CdTe as a function of the excitation power and temperature. Both bands have a nonsymmetrical shape with a gradual decrease on the high‐energy side but the variation of the shape with temperature and excitation power is different for Z‐ and Z′‐bands. Both bands have the same temperature quenching activation energy ET = 35 meV. On the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…Because of the breadth of these peaks and the variation of the stoichiometry in the near-surface region of the device, it is difficult to assign physical meaning to their origin. The emission may be related to the so-called Z and Z′ bands seen in pure CdTe 46 which have been ascribed to free-to-bound recombination near dislocations and DAP transitions within dislocation cores, but the addition of Cu has been reported to increase the intensity of the band-edge emission relative to these defect-related peaks 47 in contrast to what is observed here.…”
Section: ■ Results and Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Because of the breadth of these peaks and the variation of the stoichiometry in the near-surface region of the device, it is difficult to assign physical meaning to their origin. The emission may be related to the so-called Z and Z′ bands seen in pure CdTe 46 which have been ascribed to free-to-bound recombination near dislocations and DAP transitions within dislocation cores, but the addition of Cu has been reported to increase the intensity of the band-edge emission relative to these defect-related peaks 47 in contrast to what is observed here.…”
Section: ■ Results and Discussioncontrasting
confidence: 90%
“…45 The spectra were dominated by broad, strong defectrelated emission peaks at 1.294 and 1.203 eV for the x = 0.14 and x = 0.21 samples, which were assigned to free-to-bound and DAP transitions, respectively. 45,46 These peaks are not strongly present in our measurements. Shrestha et al also observed weak emission for the two compositions at 1.452 and 1.448 eV, respectively, which were assigned to band-to-band recombination.…”
Section: ■ Results and Discussioncontrasting
confidence: 50%
“…It is suggested that this kind of recombination gives rise to the so-called Z bands in CdTe. 7,8 The spatially curved energy gap creates a situation where defect levels within the gap are also curved, spatially, and thus the defect energy level becomes a function of the distance R from the dislocation or a grain boundary, see Fig. 5.…”
Section: ͓S0021-8979͑99͒03221-1͔mentioning
confidence: 99%
“…With an activation energy decreasing from 52 meV to 22 meV (Table 4) as the Cd/Te vapor pressure ratio decreases, and a power law dependence on the excitation (the exponent exceeding 1.88), the nature of this band according to [18] is determined by band to acceptor transitions, the last one being present on the crystallite boundary and caused probably by dislocations. The activation energies for this band is consistent to the one obtained in [18]. One cannot exclude that the Cd i 2+ to VB transitions occur (Cd i 2+ is positioned at E c -0.23 eV [17]).…”
Section: 36x-137x Ev Band 136x-137x Ev (Depending On Ratio Of CD and Tementioning
confidence: 99%